Impacts of reclaimed water irrigation on soil antibiotic resistome in urban parks of Victoria, Australia. (April 2016) - Han, Xue-Mei; Hu, Hang-Wei; Shi, Xiu-Zhen; Wang, Jun-Tao; Han, Li-Li; Chen, Deli; He, Ji-Zheng
Abstract: The effluents from wastewater treatment plants have been recognized as a significant environmental reservoir of antibiotics and antibiotic resistance genes (ARGs). Reclaimed water irrigation (RWI) is increasingly used as a practical solution for combating water scarcity in arid and semiarid regions, however, impacts of RWI on the patterns of ARGs and the soil bacterial community remain unclear. Here, we used high-throughput quantitative PCR and terminal restriction fragment length polymorphism techniques to compare the diversity, abundance and composition of a broad-spectrum of ARGs and total bacteria in 12 urban parks with and without RWI in Victoria, Australia. A total of 40 unique ARGs were detected across all park soils, with genes conferring resistance to β-lactam being the most prevalent ARG type. The total numbers and the fold changes of the detected ARGs were significantly increased by RWI, and marked shifts in ARG patterns were also observed in urban parks with RWI compared to those without RWI. The changes in ARG patterns were paralleled by a significant effect of RWI on the bacterial community structure and a co-occurrence pattern of the detected ARG types. There were significant and positive correlations between the fold changes of the integrase intI1 gene and two β-lactam resistance genes (KPC and IMP-2 groups), but no significant impacts of RWI on the abundances of intI1 and the transposase tnpA gene were found, indicating that RWI did not improve the potential for horizontal gene transfer of soil ARGs. Taken together, our findings suggested that irrigation of urban parks with reclaimed water could influence the abundance, diversity, and compositions of a wide variety of soil ARGs of clinical relevance. One-sentence summary: Irrigation of urban parks with treated wastewater significantly increased the abundance and diversity of various antibiotic resistance genes, but did not significantly enhance their potential for horizontal gene transfer. Graphical abstract: Highlights: We reported a high-throughput qPCR survey of ARGs in 12 urban parks. Diverse and abundant ARGs were detected in urban park soils. Reclaimed water irrigation impacted the patterns of ARGs. Two β-lactam resistance genes were significantly correlated with the intI1 gene. A significant effect of RWI on the bacterial community structure was observed.